Hearing Protection Success: Musicians Have a Favorable Response to Hearing Protection and Listeners Are Unable to Identify Music Produced by Musicians Wearing Hearing Protection - Nelson, Nancy L.; Killion, Mead C.; Lentz, Jennifer J.; Kidd, Gary R. (Journal of the American Academy of Audiology, 2020)
Background Musicians are known to be at risk for developing hearing sensitivity and hearing-related problems given their occupational exposure to high-level sound. Among options for hearing conservation, earplugs are an effective and inexpensive choice. Adoption rates for musicians' earplugs remains consistently low, however, given concerns about the impact of hearing protection on their own performance as well as concerns that the resultant music will be a negative experience for listeners. In fact, few studies have (1) examined musicians' attitudes about using hearing protection while performing themselves and (2) determined whether music played by musicians wearing hearing protection sounds different to listeners.Purpose The purposes of this study were (1) to evaluate how wearing musicians' earplugs affected musicians' perception of their performance while they were playing, and (2) to examine whether listeners can distinguish a difference between music recorded by musicians playing with and without earplugs.Research Design Experiment 1: student musicians were recorded playing under two conditions (with and without wearing earplugs) and then were surveyed about their experience. Experiment 2: musically experienced and naïve listeners were presented with musical samples played by musicians with and without earplugs in an ABX format. Listeners responded by indicating whether the third stimulus (X) was conditionally identical to the first (A) or second stimulus (B).Results Experiment 1: while performing, musicians always preferred the no earplugs condition. The majority, however, rated the overall experience of playing with earplugs as generally positive. Experiment 2: listeners were unable to hear a difference between the two recordings.Discussion In this experiment, musicians rated their experience playing without hearing protection more favorably than their experience playing with hearing protection, but most musicians rated their experience with hearing protection as generally positive. The inability of listeners to distinguish a difference in music played with and without hearing protection suggests that the listening experience may not be adversely impacted by hearing protection worn by the performers.Conclusion Earplugs are an inexpensive, noninvasive strategy for hearing conservation for musicians, and this study indicates that barriers to wearing hearing protection might be less problematic than previously reported.
Keywords: noise-induced hearing loss; hearing protection; musicians